1995
DOI: 10.1080/02652039509374351
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofβ‐agonists in urine and tissues by capillary gas chromatography‐mass spectrometry:In vivostudy of salbutamol disposition in calves

Abstract: The fate of salbutamol sulphate given orally has been investigated in calves. The urinary excretion rate and the tissue distribution of this beta-agonistic drug were studied by capillary gas chromatography coupled to low resolution mass spectrometry (GC-LRMS) under electron impact (EI) ionization mode, using an hexadeuterated salbutamol analogue as the internal standard. The parent drug and metabolites were extracted via solid phase extraction (SPE) mixed-phase-containing disposable columns and analysed as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…These methods include liquid chromatography (Chang, Chou, & Hwang, 2005;Meng et al, 2012;Turberg, Macy, Lewis, & Coleman, 1994), gas chromatography (Bocca, Fiori, Cartoni, & Brambilla, 2003), liquid chromatography tandem mass spectrometry (LC-MS/MS) (Shishani, Chai, Jamokha, Aznar, & Hoffman, 2003;Wu, Liu, & Peng, 2014), gas chromatography-mass spectrometry (Montrade, Lebizec, Monteau, & Andre, 1995;Wang, Li, Zhang, & Shen, 2006), enzyme-linked immunoassay (Hahnau & Julicher, 1996;Harkins, Woods, Lehner, Fisher, & Tobin, 2001;Pinheiro et al, 2008), colloidal gold test strip (Khamta, Pattarawarapan, Nangola, & Tayapiwatana, 2009;Zhang et al, 2009), surface plasmon resonance immunosensors (Traynor, Crooks, Bowers, & Elliott, 2003), and electrochemical immunosensors (He, Wang, Zhang, & Yang, 2009). Table 1 Chemical formula, accurate mass, retention time and characteristic fragment ions of 32 b-agonists.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include liquid chromatography (Chang, Chou, & Hwang, 2005;Meng et al, 2012;Turberg, Macy, Lewis, & Coleman, 1994), gas chromatography (Bocca, Fiori, Cartoni, & Brambilla, 2003), liquid chromatography tandem mass spectrometry (LC-MS/MS) (Shishani, Chai, Jamokha, Aznar, & Hoffman, 2003;Wu, Liu, & Peng, 2014), gas chromatography-mass spectrometry (Montrade, Lebizec, Monteau, & Andre, 1995;Wang, Li, Zhang, & Shen, 2006), enzyme-linked immunoassay (Hahnau & Julicher, 1996;Harkins, Woods, Lehner, Fisher, & Tobin, 2001;Pinheiro et al, 2008), colloidal gold test strip (Khamta, Pattarawarapan, Nangola, & Tayapiwatana, 2009;Zhang et al, 2009), surface plasmon resonance immunosensors (Traynor, Crooks, Bowers, & Elliott, 2003), and electrochemical immunosensors (He, Wang, Zhang, & Yang, 2009). Table 1 Chemical formula, accurate mass, retention time and characteristic fragment ions of 32 b-agonists.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of drug metabolism is of great significance to the evaluation of the efficacy and safety of clinical drugs. Some early researches reported the major metabolites of salbutamol in serum, urine, and internal tissues of animals such as calves , beef cattle , swines , rats, rabbits, and dogs . However, there are few reports on the metabolites of salbutamol in humans.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have suggested low oral bioavailability of salbutamol in rats (Montrade et al, 1995;Smith, 1998), we treated our animals with a highly concentrated solution of salbutamol (5 mg/100 ml of drinking water). Considering that treated animals consumed an average of 63 ml/day of drinking water, we estimated that the animals received a daily dose of 3.15 mg salbutamol per animal, or between about 8 and 9.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%